Analysis of the Influence of Arc Transition Oil Cavity Structure on the Performance of High-Speed Gear Hobbing Machine Hydrostatic Spindle - Li, Jinyu (International Journal of Mechanical and Electrical Engineering, 2025)
This study investigates the influence of arc transition oil cavity structure on the load-bearing characteristics of hydrostatic oil films in high-speed gear hobbing machine spindles under high-stroke conditions. By establishing fluid simulation models of oil cavity structures with different arc radii (r=0.5, 1.0, 1.5, and 2.0 mm), the effects of parameters such as eccentricity and stroke speed on oil film pressure and shear force distribution were systematically analyzed. The results demonstrate that the arc transition oil cavity structure significantly enhances the load-bearing capacity and lubrication performance of the hydrostatic oil film. Specifically, the structure with an arc radius of r=2.0 mm exhibits the most uniform pressure distribution, the lowest maximum pressure and shear force, and optimal performance. While eccentricity has a minor impact on pressure distribution, increasing eccentricity raises pressure on the eccentric side and slightly reduces it on the opposite side. At an eccentricity of 0.5, slight shear force concentration occurs on the eccentric side. Under high stroke speeds (1.0–2.0 m/s), both oil film pressure and shear force increase with speed, but the r=2.0 mm cavity structure remains the most stable, with no significant expansion of shear force concentration zones. Optimizing the oil cavity structure and employing higher supply pressure effectively improves the lubrication performance and operational stability of the hydrostatic spindle, providing theoretical and practical guidance for the design of high-speed gear hobbing machine spindles.